Analisis Pengaruh Pertumbuhan Ekonomi, Dana Alokasi Umum, Subsidi Bbm Terhadap Disparitas Pendapatan Indonesia - Anjar Noer Hartanti; M Taufiq (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research is motivated by the problem of income disparity in Indonesia which has not yet reached a low stage. There are several factors that cause income disparities to be evenly distributed or not, namely economic growth based on Kuznet's theory, general allocation funds and fuel subsidies with the initial aim of reducing income disparities which are considered not in accordance with these initial objectives. So the purpose of this study is to find out whether there is an influence from economic growth, general allocation funds and fuel subsidies on Indonesia's income disparity in the 2007-2021 period. The research method used in this study is quantitative using data on the Gini index, economic growth, general allocation funds and Indonesia's fuel subsidies for the 2007-2021 period where the data was obtained through observation by researchers. The research data were then analyzed using SPSS version 25.0 with multiple linear regression analysis techniques. The research results that have been produced in this study are that economic growth has no significant effect on Indonesia's income disparity, general allocation funds have a significant positive effect on Indonesia's income disparity and fuel subsidies on Indonesia's income disparity. Keywords: Income disparity, economic growth, general allocation fund, subsidized fuel